Features of Financial Support of Agro-industrial Complex of Kazakhstan in Conditions of WTO - AIMURZINA, Baglan; KAMENOVA, Mazken; TURSYNBAYEVA, Madina; OMAROVA, Ainura; TAZHBENOVA, Gulzhan; BEKZHANOVA, Toty (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
This article points out that the main task of state regulation of economic development of the industry in the WTO advocates a reorientation of agriculture support measures permitted by WTO rules, including optimization of structure of expenses of budgets of various levels due to reduction of programs of direct budget support, which requires the implementation of the principle of the budgeting oriented on results (BOR). The analysis of the financing of the agricultural sector from the national budget, paid attention to the credit resources allocated to the development of subjects of agricultural production. The proposals on further improvement of financial security of agrarian and industrial complex of the Republic in the WTO.